Perception of Midwives Towards Magnesium Sulfate Use at Chatinkha Maternity Wing in Blantyre, Malawi: A Qualitative Study - Chikalipo MC; Phiri LK; Mndolo N; Mbiza CR; Khisi P; Golombe E; Bonongwe P; Chirwa EM; Maluwa A (Dove Medical Press, 2020)
Maria Chifuniro Chikalipo,1 Lester Kapanda Phiri,2 Neggie Mndolo,3 Christina Ruth Mbiza,4 Patricia Khisi,4 Eunice Golombe,4 Phylos Bonongwe,4 Ellen Mbweza Chirwa,1 Alfred Maluwa5 1University of Malawi, Kamuzu College of Nursing, Blantyre, Malawi; 2University of Malawi College of Medicine, Blantyre, Malawi; 3Malawi College of Health Sciences, Blantyre, Malawi; 4Ministry of Health, Queen Elizabeth Central Hospital, Blantyre, Malawi; 5Malawi University of Science and Technology, Blantyre, MalawiCorrespondence: Maria Chifuniro ChikalipoKamuzu College of Nursing Email mchikalipo@kcn.unima.mwIntroduction: Globally, magnesium sulfate (MgSO4) has been recognized as the drug of choice for preventing and controlling fits among women with severe pre-eclampsia and eclampsia, respectively. Improper use of magnesium sulfate has been reported globally. Therefore, actionable findings for improving magnesium sulfate use are needed. This study aims at understanding the views of midwives towards MgSO4 use to inform an intervention whose objective is to improve MgSO4 use among the midwives.Methods: An exploratory qualitative study was conducted from July to September 2018. We conducted 10 in-depth interviews and a focus group discussion with midwives. All the interviews were audio taped and transcribed verbatim. Data were managed by NVivo version 10.0 and analyzed thematically.Results: We identified one overarching theme: “Inadequate governing approaches on management of clients on MgSO4” with corresponding subthemes; in adequate preparation on magnesium sulfate administration; inconsistent formula, regimen and guidelines/protocols on magnesium sulfate use and lack of resources.Conclusion: Midwives perceived MgSO4 use as a demanding activity due to inadequate training, inconsistent tools, and lack of resources. While periodic in-service training should be intensified to improve MgSO4 use, necessary resources should be provided, such as blood pressure machines, more midwives, and protocols.Keywords: magnesium sulfate, Malawi, midwives, perception and resources